Fiscal Policy Option for Abatement of Free Rider Society: The Role of Institutional Quality in Nigeria - Silva Opuala Charles; Jonah O. Orji (Mediterranean Journal of Social Sciences, 2023)
The government revenue downward trend across the globe has a serious implication on provision of public good. And the consequences of free riding manifested by tax evasion impedes social progress. In this study, we examined the Fiscal Policy Option for Abatement of Free Rider Society: The Role of Institutional Quality with special focus on Nigerian economy. We deployed Quantile Regression Technique to assess the median impact of free-riding using government expenditure on economic and social services; comprised of: defense, health, road and construction, and education. Our finding shows that expenditure on defense reduces free riding when strategically managed but encourages free riding in the long run. Same result is shown with the government expenditure on health. Whereas, expenditure on education as well as road and construction discourages free riding. Also, the moderating role of institutional quality specifically, control of corruption decreases free riding and improve tax revenue generation. Growth of free riders in any society which comes in the form of tax evasion is effectively controlled by expenditure techniques of government guided by quality of institutions. The study recommended that: A special purpose vehicle from Federal Inland Revenue Service should be created as a ‘fiscal control unit’, to monitor electronic cash registers to be connected in hospitals, public schools and social services related departments in order to curb tax leakages due to free riders. Also, government should strengthen the campaign in favour of control of corruption as well as building strong institutions; rather than building strong private individuals who posed as sacred cow in punishment for tax evasion. Received: 29 February 2023 / Accepted: 23 April 2023 / Published: 5 May 2023